Manejo do cálcio intracelular e influência da temperatura sobre a contratilidade cardíaca de Synbranchus marmoratus - Rocha, Matheus Lavorenti (Universidade Federal de São Carlos, 2004)
The present study anlyzed the in vivo and in vitro responses of the myocardium obtained from Synbranchus marmoratus acclimated at 25 ºC and tested at 15, 25 and 35 ºC. The in vivo heart rate (fH bpm) was measured during acute transitions in temperature and subsequent return to 25 ºC. ECG recordings (lead DI of the electrocardiography) were obtained of electrodes at cardiac region. Recordings of the isometric contraction force (Fc mN.mm-2) and time-dependent parameters (TPT time to peak tension; THR time to half relaxation) were obtainded in vitro from ventricle strips electrically paced in response to stimulation frequency, temperature, extracelular Ca2+, adrenaline and ryanodine (blocker of the sarcoplasmic reticulum SR). The species showed a significant increase in the fH during the transition from 25 to 35 ºC, and a significant decrease from 25 to 15 ºC, showing the importance of the chronotropic adjustments in response to thermal alterations and a great tolerance and adaptation to different thermal conditions. The species did show significant changes in the twitch force (Fc) development by the ventricular strips during the increases and decreases of temperature. The addition of crescent Ca2+ concentrations to the medium evidenced the importance of the extracellular Ca2+ for the heart contraction mainly at 35 ºC. Significant changes in the time-dependent parameters after increments in the Ca2+ extracellular concentration were not recorded. The post rest tension was conducted with and without 10 µM ryanodine in the medium. A significant post rest potentiation was recorded for the control preparations at 25 oC (100 to 119.8 ± 4.1 %) and 15 ºC (100 to 118.4 ± 2,8 %). However, this post rest potentiation was inhibited by ryanodine only at 25 oC (100 to 97.6 ± 1.5%), and, at 35 oC, force remained unchanged in the control preparations, but a significant post rest decay was recorded in the presence of ryanodine (100 to 76.6 ± 4.6%). The impact of increases in the imposed contraction frequency caused a decline of the force only at high frequencies in all the experimental temperatures. The maximal stimulation frequency sustained by the species is superior at high temperatures. The addition of a tonic level of adrenaline (10-8 M) did not cause any significant alteration in force or time-dependent parameters, when compared to control values. However, in presence of the 10 µM ryanodine, the Fc decreased significantly, without alteration in the TPT and THR. Additionally, the adrenaline concentration was incresed to 10-5 M. The adrenergic stimulation with high level of adrenaline caused positive inotropy with a magnitude that ameliorated the negative inotropic effect of ryanodine, with the exception of high pacing frequencies. In conclusion, S. marmoratus seems to possess large stores of intracellular activator Ca2+, resembling mammals rather than terrestrial ectothermic vertebrates. As a difference, this species also depends on extracellular sources of Ca2+ at high temperatures which provide more flexibility to modulate the contraction force.
Keywords: Fisiologia comparada; Retículo sarcoplasmático; Acoplamento E-C; Temperatura; Relação força-frequência; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA COMPARADA